Implementasi Database SQLite pada Data Mahasiswa Universitas Labuhanbatu Berbasis Android - Pasaribu, Riski Febriyan; Azhari, Fitrialdi (Jurnal Gemilang Informatika (GIT), 2023)
In the manual process, sometimes there are several data archives that experience recording errors, do not include student report data that is not recorded properly, there are even some archives that experience loss. Based on this background, a research was conducted on the optimal computerized application of student data at Labuhan Batu University. Methods Research conducted using the Waterfall Methodology. Applications are software used for specific purposes, such as processing documents, managing Windows and games. A smartphone is a mobile phone that combines the functions of a Personal Digital Assistant (PDA). Android is a Linux-based mobile device operating system that includes an operating system, middleware and applications. Eclipse IDE is an IDE (Integrated Development Environment) for developing software and can be run on all platforms. SQLite is an ACID-compliant database. UML is a tool/model for designing object-oriented software development.